Satisfaction Level of Rural Youth Regarding Trainings on Practical Education in Agriculture - Singh, Kulwant; Kalra, Rajinder Kaur (Indian Journal of Extension Education, 2021)
The study was conducted to investigate the nature and extent of problems and the satisfaction level of trainees of three month course on ‘Practical education in agriculture for rural youth in Punjab’. The data were collected from 80 trainees through a semi-structured questionnaire, pre-tested on 10 respondents. These results revealed that >80 per cent of the respondents were satisfied with the timings of training course, topics covered, time devoted to each topic, lecture-cum-discussion method, distribution of literature, visits of model farms, skills in handling of audio visual aids, relevant and usefulness of the course content. About 82.9 per cent of respondents’ perceived lack of provision notes as major problem associated with practical education. The other problems associated with effective execution of trainings were insufficient duration of field demonstration, inadequate availability of audio visual aids, insufficient seating arrangements, inadequate boarding, drinking water and transportation facilities. About 2/3rd of total respondents suggested a ratio of 40: 60 for theory: practical for effective transmission of the information to the trainees.
Keywords: Satisfaction; ield demonstrations; Transportation facility; Course duration